Change Engagement, Change Resources, and Change Demands: A Model for Positive Employee Orientations to Organizational Change - Albrecht, Simon L.; Connaughton, Sean; Foster, Kathryn; Furlong, Sarah; Yeow, Chua Jim Leon (Frontiers in Psychology, 2020)
The purpose of this conceptual paper is to introduce the construct of change engagement, and a model which also consists of change-related organizational resources, change-related job resources and demands, and change-related personal resources. We propose that change engagement is a construct that is theoretically and practically useful for understanding employee reactions to and adoption of organizational change. Drawing from existing models of employee engagement, we add to the change literature by identifying salient change-related organizational resources, job resources, job demands and personal resources in a previously validated framework that brings together the literature on both engagement and change. By using the proposed change engagement framework practitioners and researchers will potentially be able to effectively diagnose, manage, and optimize employee change readiness and enthusiasm for ongoing change. Furthermore, the change engagement model provides practitioners and researchers with a comprehensive and practically useful model that will be easy to comprehend and communicate. The model can be applied to the planning, implementation and evaluation of discrete change initiatives as well as to ongoing change. The model is therefore well-suited to contemporary organizational contexts where change is widely recognized to be a constant.